Synthesis and characterization of molecularly imprinted polymer embedded composite cryogel discs: application for the selective extraction of cypermethrins from aqueous samples prior to GC-MS analysis. Issue 34 (15th April 2015) - Shaikh, Huma; Andaç, Müge; Memon, Najma; Bhanger, Muhammad Iqbal; Nizamani, Shafi Muhammad; Denizli, Adil
<x xml:space="preserve">Abstract</x> Molecularly imprinted particles embedded composite cryogel discs specific for α-cypermethrin and β-cypermethrin were prepared.